Redefining the Surface Anatomy of Major Abdominal Structures in an Adult Population: A Computed Tomography Evaluation - Masroor Badshah; Muhammad Ibrahim; Khaled A. Elnahriry; Roger Soames (Clinical Anatomy, 2026)
ABSTRACT Inconsistencies exist in anatomy and clinical reference texts regarding the vertebral levels of major abdominal structures. Accurate surface anatomy is essential for diagnostic interpretation and interventional procedures, yet little is known about how health status or pathology may influence the vertebral relationships of abdominal organs. This study aimed to compare the projected surface anatomy of major abdominal structures in a healthy adult population with that in an age‐ and gender‐matched population with abdominal pathology using computed tomography. Sixteen‐slice CT scans from 95 healthy individuals and 70 with abdominal pathology were analyzed with a DICOM viewer to determine the vertebral levels of 20 abdominal structures (liver; kidneys and renal hilum; spleen; abdominal aortic bifurcation; renal, celiac, superior mesenteric, and inferior mesenteric arteries; portal and splenic veins; psoas major; and the umbilical plane). Binary logistic regression was applied to assess associations between health status and vertebral level. Significant associations were observed between health status and vertebral level for the inferior pole of the left kidney (odds ratio [OR] 1.33, 95% CI 1.01–1.76, p = 0.041) and the origin of psoas major (OR 1.59, 95% CI 1.12–2.26, p = 0.007). From this, it is concluded that the vertebral levels of several abdominal structures vary between healthy individuals and those with abdominal pathology, particularly the left kidney and psoas major. These findings highlight the need to revisit abdominal surface anatomy descriptions in clinical reference texts using modern imaging, ensuring greater accuracy for clinical practice and education.